ANALYSIS OF IRRIGATED SOILS OF THE BUKHARA OASIS (Scientific journal of the Fergana State University, 2025)
The article describes in detail the classification of the main irrigated soils distributed in the Bukhara oasis, including old irrigated swamp-meadow, barren meadow, barren, barren, barren-meadow, sandy-desert, gray-brown, gray-brown meadow soil types.